Characteristics of soil pollution and element migration associated with the use of coal in Hutou Village, Yunnan Province, China. (June 2022) - Chen, Zailin; Shi, Zeming; Ni, Shijun; Cheng, Long
Highlights: There was severe Cd and Cr pollution in the soil of Hutou Village. The primary source of soil pollution was the use of coal. Mineralogical and geochemical characteristics revealed the migration direction of the pollution. The contents of REY and Eu in the soil were significantly higher than those in road dust. The fractionation of LREY and HREY in the soil was more substantial than that in the road dust. Abstract: This study aimed to reveal the status and source apportionment of trace element soil pollution in a village with a relatively high incidence of lung cancer in China and determine the element migration characteristics from coal to road dust and soil. To this end, 24 soil samples, 48 road dust samples (from a previous study), and 2 coal samples were collected; major element oxides, V, Cr, Co, Ni, Cu, Zn, Zr, Cd, and rare earth elements were analyzed; minerals were identified by SEM-EDX and XRD; a geoaccumulation index (Igeo ), Spearman's correlation analysis, provenance index (PI) and positive matrix factorization (PMF) were carried out to assess the status and source apportionment of soil pollution; and mineralogical and geochemical methods were used for provenance discrimination and migration characteristics identification. The results demonstrated that (1) the Cd and Cr pollution of the soil was severe and originated mainly from indigenous zinc smelting, agricultural activities, and the use of coal. (2) The pollution migrated from Yantang coal to the road dust to the soil through mineralogical and geochemical methods. (3) A stronger fractionation of light and heavy rare earth elements was observed in the soil than in the road dust, indicating a single pollution source in the road dust and a complex source in the soil. (4) The primary reason for the lower rare earth element values in the road dust could be physical separation by the wind.